Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1001/jamaophthalmol.2020.3190
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Autonomous Point-of-Care Diabetic Retinopathy Screening for Pediatric Patients With Diabetes

Abstract: ouths and adults with diabetes are at risk for diabetic retinopathy (DR), which can lead to vision loss. 1 The prevalence of DR among youths with type 1 diabetes (T1D) and type 2 diabetes (T2D) ranges from 4% to 13%. [2][3][4] Despite recommendations from the American Diabetes Association and American Academy of Ophthalmology for yearly screening, adherence remains low. 5 Although the prevalence is low among youths, the risk of developing DR is high. Diabetic retinopathy is present in up to 50% of patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 35 publications
1
51
0
Order By: Relevance
“…20 Although a dilated and comprehensive eye examination by an ophthalmologist remains the standard of care for retinal screening, fundus photography with or without artificial intelligence-based techniques for point-of-care detection of DR serves as an accurate screening tool for DR, is feasible for use among young patients with diabetes, increases adherence to recommended screening, and is cost-effective. [23][24][25][26][27][28] Our study sought to estimate the burden of DR among children, adolescents, and young adults in the US at the time of point-of-care DR screening and to identify factors associated with DR by combining data from 2 large pediatric hospitals that have robust DR screening programs. Combining data from these 2 sites allowed us to report findings from analyses that, to our knowledge, include one of the largest and most racially diverse groups of young patients with type 1 and type 2 diabetes in the US.…”
Section: Introductionmentioning
confidence: 99%
“…20 Although a dilated and comprehensive eye examination by an ophthalmologist remains the standard of care for retinal screening, fundus photography with or without artificial intelligence-based techniques for point-of-care detection of DR serves as an accurate screening tool for DR, is feasible for use among young patients with diabetes, increases adherence to recommended screening, and is cost-effective. [23][24][25][26][27][28] Our study sought to estimate the burden of DR among children, adolescents, and young adults in the US at the time of point-of-care DR screening and to identify factors associated with DR by combining data from 2 large pediatric hospitals that have robust DR screening programs. Combining data from these 2 sites allowed us to report findings from analyses that, to our knowledge, include one of the largest and most racially diverse groups of young patients with type 1 and type 2 diabetes in the US.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining 20 studies were read full text. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The relevant data were extracted and the 2 reviewers independently further assessed the quality of the articles per the CHEERS and Philips checklists.…”
Section: Search Resultsmentioning
confidence: 99%
“…A general overview of the included studies, including the details of the reported AI applications, is provided in Table 2. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The majority of studies was published in 2019 or later. The studies were conducted in a range of medical specialties, yet ophthalmology was evidently the dominant field.…”
Section: General Overview Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations